Sejarah perkembangan tasawuf - Setiorini, Faradina (Maliki Interdisciplinary Journal, 2024)
In the course of 14 centuries, a very influential view of life has grown in Islam. This view is the Sufism movement or Sufism. The influence that the Sufism movement has had on the lives of Muslims is clear. Sometimes you encounter influences that make your soul great, and sometimes you also encounter other influences which, when compared with the original Islamic teachings, will appear to be very different. This article aims to invite readers to know more about the truth of the development of Sufism and understand how Sufism has developed from time to time. Apart from that, this article also aims to make it easier for readers to find sources about the history of the development of Sufism. Sufism is part of Islamic law whose teaching focuses on purifying the soul with the aim of closeness, love and unity with Allah Swt.